The anti-inflammatory role of extranuclear apurinic/apyrimidinic endonuclease 1/redox effector factor-1 in reactive astrocytes. Issue 1 (December 2016) - Baek, Hyunjung; Lim, Chae; Byun, Hee; Cho, Hyun; Lee, Yu; Shin, Yong; Kim, Hyun-Woo; Jeon, Byeong; Kim, Dong; Hong, Jinpyo; Hur, Gang; Park, Jin
Abstract Apurinic/apyrimidinic endonuclease 1 (APE1), a ubiquitous multipurpose protein, is also known as redox effector factor-1 (Ref-1). It is involved in DNA repair and redox signaling and, in turn, oxidative stress-induced neurodegeneration. Although previous studies have demonstrated that APE1/Ref-1 functions as a negative regulator of inflammatory response via several mechanisms in neuronal cells, little is known about the roles of APE1/Ref-1 in glial cells. In this study, we found that cytoplasmic APE1/Ref-1 expression was upregulated in reactive astrocytes of the kainic acid- or lipopolysaccharide (LPS)-injected hippocampus. Analysis of the inflammatory response induced by extranuclear APE1/Ref-1 (ΔNLS-Ref-1) in cultured primary astrocytes revealed that it markedly suppressed inducible nitric oxide synthase (iNOS) expression and tumor necrosis factor-α (TNF-α) secretion induced by LPS to a similar extent as did wild type APE1/Ref-1 (WT-Ref-1), supporting the concept an anti-inflammatory role of extranuclear APE1/Ref-1 in astrocytes. Additionally, overexpression of WT- and ΔNLS-Ref-1 suppressed the transcriptional activity of nuclear factor-κB (NF-κB), although it effectively enhanced activator protein 1 (AP-1) activity. The blunting effect of APE1/Ref-1 on LPS-induced NF-κB activation was not mediated by IκB kinase (IKK) activity. Instead, APE1/Ref-1 inhibited p300-mediated acetylation of p65 by suppressing intracellular reactive oxygen species (ROS) levels following LPS treatment. Taken together, our results showed that altered expression and/or subcellular distribution of APE1/Ref-1 in activated astrocytes regulated the neuroinflammatory response to excitotoxin and endotoxin insults used in model of neurodegenerative brain diseases.